Використання методу аналітичних угрупувань при управлінні виробничим потенціалом підприємства - Савченко, Ольга Ігорівна; Верютіна, Вікторія Юріївна (НТУ "ХПІ", 2014)
У статті розглянуто сутність ефективності застосування економіко-математичних моделей. Охарактеризовано основні фактори, що впливають на економічну ефективність використання ресурсів: обсяг виробництва, продуктивність праці, фондовіддача, технічний та організаційний рівень виробництва, матеріальні витрати. Здійснено аналіз використання виробничого потенціалу та визначено нові перспективні прогнозовані показники діяльності підприємства.

The article deals with the essence of the effectiveness of economic and mathematical models. Describes the main factors that influence the cost-effectiveness of the use of resources: the volume of production, labor productivity, capital productivity, technical and organizational level of production and material costs. The analysis of the use of productive capacity and identify promising new forecast indicators of the company. The paper analyzes the internal characteristics of technological potential of the enterprise. To enhance the management presents classification technologies. Identified the need for additional indicators that are associated with innovation activity of enterprises, protection of rights to intellectual property. Adaptive potential of the enterprise is defined from the perspective of the development of technological resources of the enterprise. Conclusions and recommendations to improve the effective management of production potential.
The use of analytical groups in the production management potential of the enterprise
Keywords: економіко-математичні моделі; економічна ефективність; адаптаційний потенціал; управлінські заходи; прогнозовані показники; production potential; economic efficiency; method of analytical groups; adaptive potential